A CONTENT ANALYSIS OF DIGITAL REPRESENTATION IN INDONESIAN SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Fathur Rahman; Dewi Sri Wahyuni (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
This study examines how digital representations are incorporated into the English textbook for senior high school students in Indonesia titled Life Today (2022), published by the Ministry of Education, Culture, Research, and Technology. Given rapid technological advancements, English language curricula should reflect how digital technologies are integrated into learning and support the development of students’ digital literacy. It remains unclear how much digital content is covered in the book. This study employs qualitative content analysis of the book’s 24 sections, highlighting three main aspects: digital devices, digital activities, and digital culture. Findings indicate the presence of digital elements, though they are not evenly distributed across all chapters and sections. Digital activities appear with increasing frequency, while digital devices and cultural elements are not always presented consistently. Furthermore, digital elements mostly appear through tasks requiring responses, which tend to hinder students’ active participation. The absence of interactive digital features indicates that the textbook emphasizes conceptual understanding over engaging students in digital activities. These results underscore the need for a more structured and balanced approach to integrating digital practices into the curriculum, so that students can improve their digital literacy more effectively.